PENINGKATAN KEMAMPUAN MENULIS PUISI MENGGUNAKAN PENDEKATAN KONTEKSTUAL PADA SISWA KELAS VII SMPN 3 SELUAS - Beli, Hermina; Abdussamad, Abdussamad; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis class action research was motivated by the low skill in writing rhym texts in class VII A. The low skill in reading pantun texts in grade VII students of SMP Negeri 3 Seluas was caused by several factors, the first factor the students are difficult to determine ideas or themes in writing rhymes, second factor the students are difficult to develop ideas because of the lack of mastery of vocabulary, and the third factor the students are not used to pouring their imagination in a writing. The purpose of this class action research are aims to find out the application of contextual learning approaches to improve learning outcomes in writing pantun texts in grade VII A students in SMP Negeri 3 Seluas. This research is a Classroom Action Research (CAR) using a contextual approach with the following stages; 1) planning, 2) implementation / observation, 3) reflection. This research was conducted at SMP Negeri 3 Seluas with research subjects in class VII A academic years 2018/2019, there areÂ  26 students in the class. This research is descriptive, and the method is a qualitative form. Based on the results of data analysis showed that there was an increase from cycle I to cycle II. This can be seen from the average value of students in each cycle. The average value of students in the first cycle 68.25 with enough categories while the average value of students in the second cycle is 96.5 with a very good category.Keywords: rhymes writing skills, contextual approach